2022
DOI: 10.1080/13696998.2022.2087409
|View full text |Cite
|
Sign up to set email alerts
|

A head-to-head comparison of EQ-5D-5L and SF-6D in Dutch patients with fractures visiting a Fracture Liaison Service

Abstract: Aims: This study compared the psychometric properties of EQ-5D-5L and SF-6D to assess the interchangeability of both instruments in patients with a recent fracture presenting at a Fracture Liaison Service (FLS). Materials and methods: Data from a prospective observational study in a Dutch FLS clinic were used. Over 3 years, subjects were interviewed at several time points using EQ-5D-5L and SF-36. Floor and ceiling effects were evaluated. Agreement was evaluated by intra-class correlation coefficients and visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The ceiling effect of EQ-5D-5L was evident as the NYHA cardiac function class improved after discharge. Our follow-up results showed a higher ceiling effect [26]. The disease’s morbidity level is thought to be a possible factor influencing the ceiling effect in EQ-5D [27].…”
Section: Discussionmentioning
confidence: 99%
“…The ceiling effect of EQ-5D-5L was evident as the NYHA cardiac function class improved after discharge. Our follow-up results showed a higher ceiling effect [26]. The disease’s morbidity level is thought to be a possible factor influencing the ceiling effect in EQ-5D [27].…”
Section: Discussionmentioning
confidence: 99%
“…The SF-6Dv2 has a DCE with duration-based value set for the UK in contrast to the standard gamble used for the SF-6Dv1 [ 82 ]. Nevertheless, in some studies across diverse populations, the SF-6Dv1 demonstrated comparable validity to the EQ-5D-5L [ 83 86 ]. Comparing the outcomes of cost–utility analyses using these instruments appears to be an important future research direction.…”
Section: Discussionmentioning
confidence: 99%